Contribution of ground-floor activity to the touristification of public spaces: The Historic Centre of Genoa as a case study (Ciudades, 2025)
Commercial gentrification and the privatisation of public space are two characteristics of the touristification of historic port cities. The literature has studied these variables independently, but an integrated approach is necessary to determine the relationship between ground-floor activity and touristification. To identify the main public spaces touristified by ground-floor activity, this research develops a methodology based on indicators that combine these variables from the public space unit. Testing this methodology in the city of Genoa has enabled the identification of four areas specificallytouristified by ground-floor activity.
Keywords: turistification; indicators; privatization of public space; urban planning; historic centre; commercial gentrification